The Effectiveness of Red Bread Leaves on the Healing of Perineum Wound - Debi Novita Siregar; Titin Sundari Nazara; Morina Sinaga (Jurnal Penelitian Perawat Profesional, 2020)
Perineal wound is a tear in the birth canal or due to an incision made in the perineum during delivery of the fetus. Perineal wound treatment can be done with traditional treatments, namely by using herbal medicines, for example making red betel leaf boiled water as washing water or personal hygiene that can be used. used in healing perineal wounds because in boiled water red betel leaf has many properties and contains many active compounds. The purpose of this study was to determine the effectiveness of red betel leaf decoction in healing perineal wounds. This research method is quantitative analytic observational with this type of research design using a quasi experimental method with a pretest posttest one group design. The study was conducted on 10 August to 25 August 2020 with a sample of 30 people using the total sampling technique. Aspects of data measurement using observation sheets with data analysis. The results showed that all respondents (100%) experienced healing of perineal wounds. The results of data analysis obtained Z value = -4460b and p-value = 0.000 with a significance level of p <0.05